2011
DOI: 10.1002/wcs.125
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian approaches to sensory integration for motor control

Abstract: The processing of sensory information is fundamental to the basic operation of the nervous system. Our nervous system uses this sensory information to gain knowledge of our bodies and the world around us. This knowledge is of great importance as it provides the coherent and accurate information necessary for successful motor control. Yet, all this knowledge is of an uncertain nature because we obtain information only through our noisy sensors. We are thus faced with the problem of integrating many uncertain pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 67 publications
5
50
0
Order By: Relevance
“…Thus, it is also possible that the perception of causality between an action and its outcome is one of the decisive factors for the acquisition of their statistical relation. Other lines of evidence have suggested that causality inference between events plays critical roles in the optimal integration of cross-sensory signals (Körding et al, 2007; Sato et al, 2007; Berniker and Körding, 2011). As such, we suggest that the perception of causality between an action and its outcome at least partly underlies the acquisition of the statistical relation between them, though we need to empirically dissociate the contribution of action from non-action factors to the acquisition of an action-effect relation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is also possible that the perception of causality between an action and its outcome is one of the decisive factors for the acquisition of their statistical relation. Other lines of evidence have suggested that causality inference between events plays critical roles in the optimal integration of cross-sensory signals (Körding et al, 2007; Sato et al, 2007; Berniker and Körding, 2011). As such, we suggest that the perception of causality between an action and its outcome at least partly underlies the acquisition of the statistical relation between them, though we need to empirically dissociate the contribution of action from non-action factors to the acquisition of an action-effect relation.…”
Section: Discussionmentioning
confidence: 99%
“…The Bayesian paradigm has been viewed as an extension of logic that enables reasoning with propositions whose truth or falsity is uncertain [54,55]. In cognitive science, it has successfully accounted for a wide range of observations, including cue combination in humans [5,4,1,56,3,6,7,2], sensorimotor control [8,9,57], integration of temporal statistics [35,34,10,11,36], perceptual multistability [58,39,40], and various aspects of cognition [59,60,61,38,62].…”
Section: Online Bayesian Inferencementioning
confidence: 99%
“…the prior) with a measured observation (the likelihood) to update predictions of the current state of the system (the posterior probability). Kalman filters have found several applications, for example, in aeronautics and in humanoid robotics (see references in Berniker and Körding, 2011) and they have been used also in neuroscience, to develop neuro-physiological models of motor controls (Berniker and Körding, 2011).…”
Section: A Bayesian Sequential-sampling Model Of Choicementioning
confidence: 99%